Characterization of pulse forming networks / Ariffuddin Joret - Joret, Ariffuddin (1998)
Pulse Power Technology is another subdivision being embarked recently. This field is very synonym to High Voltage Engineering, which deals with thousands of volt in small range of current. The generation of high voltage impulse is a prime requirement prior to the actual testing process. Impulse signal could be generated using solid-state devices and even to the application of coaxial cable, which is capable in producing high voltage impulse. This set-up is widely known as Pulse Forming Networks (PFN). This thesis presents the characteri zation of PFN model using coaxial cable, simulation through Microcap5 and experimentation of various models. Various construction of PFN were carried out such as Single Pulse Forming Line, Open Transmission Line and Stacked-Blumlein Generator. Results obtained from the laboratory experiment indicated that an agreement with the theoretical prediction is accomplished.